Foreign Ownership and Market Power in Banking: Evidence from a World Sample. Issue 2 (March 2016) - DELIS, MANTHOS D.; KOKAS, SOTIRIOS; ONGENA, STEVEN
Abstract : The nexus between ownership and competition in the banking sector is a major concern to policymakers around the world but one that is rarely comprehensively examined. For 131 countries and 13 years we match bank ownership with over 50, 000 bank‐year estimates of individual bank market power. We find that ownership does not explain market power at the individual bank level. However, at the country level, foreign bank ownership has a positive and significant impact on market power mainly because foreign banks enter through mergers or acquisitions and not through greenfield investments. The observed increases in market power primarily originate from decreases in the marginal cost.